PENEGAKAN HUKUM TERHADAP PELAKU PENYEBARAN KONTEN PORNOGRAFI DI MEDIA SOSIAL (REVENGE PORN) - Muhammad Rizky Septiadi Santoso (2023)
Terror that threatens, the right to choose religion and belief is a fact that often befalls people around the world. The right to defend, as well as the right to choosea religion of belief is indeed a right for all people in all parts of the world. choosing a religion of belief is crucial to achieving peace and stability in all parts of the world, as happened on March 15, 2019, the world was shocked by the horrific shooting terror at two mosques in New Zealand. The perpetrator Brenton Harrison Tarrant (28) viciously opened fire on the congregation of the mosque who were praying Friday. This incident took place at the Al Noor Mosque and the Linwood Mosque in Christchurch, New Zealand. In this case the author will discuss what is the topic raised by the author, namely the element of human rightsviolations from the shooting action in the form of a violation of Article 28 of the Universal Declaration of Human Rights (UDHR) and the treatment of the perpetrators which includes the crime of genocide, then also how the Prime Minister of Zealand recently carried out diplomatic efforts in the form of Alternative Dispute Resolution (ADR) between countries whose citizens became victims in the case. This was deemed successful because the Prime Minister of New Zealand was able to prevent inter-religious conflicts between worlds, and explained to the whole world that we must eliminate the attitude of Islamophobia, or fear of Muslims who are considered terrorists, but in fact it is a wrong teachingand Islam is not the same once taught about acts of Terrorism.